(untitled) (Balthazar, 2022)
In his preface to the French edition of his book Comunismo queer, published by Syllepse in 2022, written during the months of lockdown due to the pandemic, Federico Zappino recalls the position he adopts throughout this essay, where heterosexuality is conceived, thought out and analyzed as a “mode of production”: a radically materialist, anti-essentialist and anti-identitarian perspective. The recourse to this concept of the Marxian lexicon is functional not only to frame oppression, violence and gender and sexual inequality in materialistic terms, but also to think of their definitive subversion.